Exploiting in situ antigen generation and immune modulation to enhance chemotherapy response in advanced melanoma: A combination nanomedicine approach. Issue 1 (28th August 2016) - Lu, Yao; Wang, Yuhua; Miao, Lei; Haynes, Matthew; Xiang, Guangya; Huang, Leaf
Highlights: A lot of clinically relevant cancers lack ideal targets. Chemotherapy-induced apoptosis for in situ antigen generation could enhance TLR agonist. Lipid-coated cisplatin nanoparticles (LPC) and CpG-encapsulated liposomes (CpG-Lipo) were prepared. LPC+CpG-Lipo combination therapy exhibited synergistic CTL response. LPC+CpG-Lipo combination therapy established strong synergistic effect in abrogation of tumor growth. Abstract: Therapeutic anticancer vaccine development must address a number of barriers to achieve successful tumor specific killing, including effective antigen presentation and antigen-specific T-cell activation to mediate cytotoxic cellular effects, inhibition of an immune-suppressive tumor microenvironment in order to facilitate and enhance CTL activity, and induction of memory T-cells to prolong tumor rejection. While traditional as well as modern vaccines rely upon delivery of both antigen and adjuvant, a variety of clinically relevant cancers lack ideal immunogenic antigens. Building upon recent efforts, we instead chose to exploit chemotherapy-induced apoptosis to allow for in situ antigen generation in a combination, nanomedicine-based approach. Specifically, lipid-coated cisplatin nanoparticles (LPC) and CpG-encapsulated liposomes (CpG-Lipo) were prepared for the temporally-controlled and multifaceted treatment of an advanced in vivo model of melanoma. Such combination therapy established strong synergistic effects, both in apoptotic extent and subsequent abrogation of tumor growth, which were due largely to both an enhanced cytotoxic T-cell recruitment and a reduction of immune-suppressive mediators in the microenvironments of both spleens and tumor. These results underlie a prolonged host lifespan in the combination approach (45 days) as compared with control (25 days, p < 0.02), providing promise toward a personalized approach to nanomedicine by establishing effect synergy in host-specific immunotherapy following chemotherapy.